2020
DOI: 10.1001/jamanetworkopen.2020.4315
|View full text |Cite
|
Sign up to set email alerts
|

Association of Participation in an End-of-Life Conversation Game With Advance Care Planning Behavior and Perspectives Among African American Individuals

Abstract: IMPORTANCE Less than 25% of African American individuals have completed advance directives and are thus vulnerable to poor end-of-life care. Low-cost interventions are needed to increase engagement in advance care planning (ACP).OBJECTIVES To investigate whether an end-of-life conversation game motivates African American attendees to engage in ACP and to assess whether the game is well received and endorsed.EXPOSURES Attendance at an end-of-life conversation game (Hello) played in groups of 4 to 6 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(87 citation statements)
references
References 60 publications
(138 reference statements)
0
73
0
Order By: Relevance
“…Quantitative assessment of this game-based conversation intervention showed that the game was useful, provided new information and perspective, was emotionally beneficial, and empowered and motivated them to perform advance care planning. 269 Future research should encourage new approaches leading to more systematic implementation of advance care planning. Tools to increase integration of advance care planning decisions into care should be explored, especially those that are technologically based.…”
Section: Frequency Of Service Attendance and Completion Of Advance Directives Among Non-hispanic Blacksmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative assessment of this game-based conversation intervention showed that the game was useful, provided new information and perspective, was emotionally beneficial, and empowered and motivated them to perform advance care planning. 269 Future research should encourage new approaches leading to more systematic implementation of advance care planning. Tools to increase integration of advance care planning decisions into care should be explored, especially those that are technologically based.…”
Section: Frequency Of Service Attendance and Completion Of Advance Directives Among Non-hispanic Blacksmentioning
confidence: 99%
“… 25 Van Scoy and colleagues (2020) evaluated an hour video-based low-cost end-of-life conversation game to motivate non-Hispanic Blacks to complete advance care planning. 269 Game events were held in 53 community venues across the United States. During this intervention participants played a conversation game that prompted players to answer and discuss 20 questions about death, dying, and end-of-life care.…”
Section: Completion Of Advance Care Planning and Directivesmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Moreover, 16%–80% of participants reported signing an advance directive, updating the existing ones, or designating a healthcare proxy at follow-up in four studies. 28,31,32,34…”
Section: Resultsmentioning
confidence: 99%
“…40 By using serious illness communication tools tailored around the needs of persons at risk for poor COVID-19 outcomes, clinicians in primary and specialty care can lead these discussions across settings-including at home and in long-term care, nursing homes, dialysis centers, and other nonacute places of care before patients become severely ill. [40][41][42] Engaging Black Americans and other racial/ethnic minorities in a tailored community-based communication intervention-for example, at churches or social service organizations where mistrust of healthcare systems may not be as strong a barrier-may increase prevalence of these discussions in minority communities before patients are hospitalized. [43][44][45][46] These discussions can also be conducted via telehealth technology, a platform patients and clinicians have rapidly adopted during the pandemic. 47,48 When patients, families, or surrogate decision-makers cannot be physically present to discuss treatment options with clinicians, telecommunication discussions help meet patient needs 24 while restoring a sense of human connection in difficult social distancing circumstances.…”
Section: Perspectivementioning
confidence: 99%